First Results and Prospects of a New Approach to the Study of Active Geologic Processes by Space and Ground Instrumental Measurements (by the Example of Kamchatka and the Central Asian Orogenic Belt) - Dobretsov, N.L.; Buslov, M.M.; Vasilevskiy, A.N.; Zhmodik, S.M.; Kotlyarov, A.V. (Russian geology and geophysics, 2021)
––The use of satellite-geological information permits generalization of studies of various active geologic processes in a new way. As reference examples, we consider geologic regions extensively covered by research with our contribution. The joint use of satellite images, maps of gravity anomalies, and seismic-tomography data for Kamchatka made it possible to construct 3D models of surficial and deep-seated (depths from 10–50 to 650 km) volcanic structures. For young volcanosedimentary structures of Kamchatka, it is possible to trace the interaction of various processes, from crystallization of magmas in magma chambers to ore and oil formation in calderas. Ancient tectonic structures and superposed Cenozoic deformations in the Tien Shan, Altai, and Baikal regions are clearly displayed in satellite images and on maps of gravity anomalies. The long-range impact of the Indo-Eurasian collision on the Tien Shan, Altai, and Baikal regions was expressed as shearing, which resulted in the most contrasting structures in the zones of junction of regional faults and along the framing of cratonal structures. The active structures of Gorny Altai contain numerous travertines, whose abundance is correlated with seismic activity. The mass formation of methane and gas hydrates in Lake Baikal might be related to mantle plume fluids.